The mediating role of college students' body image and self-esteem in the impact of physical activity on life satisfaction and mental health - Xiaoli Liu; Liting Liu (Acta Psychologica)
Background: As mental health and life satisfaction gain attention, college students increasingly recognize their impact on well-being. Physical activity is known to improve mental health and life satisfaction, potentially mediated through self-cognitive factors like body image and self-esteem. The effect of physical activity on psychological outcomes may differ by gender. Methods: A random sample of 712 college students was surveyed using the Physical Activity Rating Scale, Body Esteem Scale for Adolescents and Adults, Rosenberg Self-Esteem Scale, Chinese Life Satisfaction Scale, and Chinese Mental Health Questionnaire. Data were analyzed using SPSS 26.0 software to assess the direct and mediating effects of physical activity and the moderating role of gender. Results: Physical activity significantly improved mental health (β = 0.0229, p < 0.001) and life satisfaction (β = 0.0377, p < 0.001). Body image mediated the effect on mental health (β = 0.0090, p < 0.01) and life satisfaction (β = 0.0121, p < 0.001). Self-esteem also mediated the relationship with mental health (β = 0.0019, p < 0.05) and life satisfaction (β = 0.0027, p < 0.001). The impact of physical activity on self-esteem was significantly stronger in females. Conclusion: Physical activity directly enhances college students' mental health and life satisfaction and indirectly affects them by improving body image and self-esteem. Gender moderates certain pathways, suggesting tailored interventions for different genders. These findings provide theoretical and empirical support for integrating physical activity with mental health development in universities.